What makes me tick in the pan(dem)ic - Kulkarni, Uma (Research and Humanities in Medical Education, 2020)
The "pandemic" has come with "panic" embedded within it. The panic among health care workers is enormous. There is a fear of being infected and carrying the infection home to their children and to the extended family. There is a constant tussle between overcoming these fears and stepping forward to take up responsibilities and duties. The article is a narrative of an ophthalmologist trying to think right and doing what best she can in times of the pandemic.